2001
DOI: 10.1017/s0022029901005210
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and microbiological characterisation of kefir grains

Abstract: Chemical and microbiological composition of four Argentinean kefir grains from different sources as well as characteristics of the corresponding fermented milk were studied. Kefir grains CIDCA AGK1, AGK2 and AGK4 did not show significant differences in their chemical and microbiological composition. In contrast, protein and yeast content of AGK3 was higher than in the other grains. Although grain microflora comprised lactobacilli, lactococcus, acetic acid bacteria and yeast, we found an important difference re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
200
3
34

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 290 publications
(262 citation statements)
references
References 27 publications
10
200
3
34
Order By: Relevance
“…bulgaricus (Yuksekdag et al 2004b); Lb. parakefir (Garbers, Britz, & Witthuhn, 2004;Garrote, Abraham, & De Antoni, 2001) (Yuksekdag et al, 2004a); Pediococcus acidilactici, P. dextrinicus, P. pentosaceus (Sabir et al, 2010); Acetobacter aceti (Motaghi et al, 1997); A. lovaniensis (Magalhaes et al, 2011a); and A. syzgii (Miguel et al, 2010). Witthuhn et al (2004) reported that LAB and yeast levels present in kefir grains vary widely, ranging from 6.4 × 10 4 to 8.5 × 10 8 and 1.5 × 10 5 to 3.7 × 10 8 cfu/mL, respectively.…”
Section: Microbiological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…bulgaricus (Yuksekdag et al 2004b); Lb. parakefir (Garbers, Britz, & Witthuhn, 2004;Garrote, Abraham, & De Antoni, 2001) (Yuksekdag et al, 2004a); Pediococcus acidilactici, P. dextrinicus, P. pentosaceus (Sabir et al, 2010); Acetobacter aceti (Motaghi et al, 1997); A. lovaniensis (Magalhaes et al, 2011a); and A. syzgii (Miguel et al, 2010). Witthuhn et al (2004) reported that LAB and yeast levels present in kefir grains vary widely, ranging from 6.4 × 10 4 to 8.5 × 10 8 and 1.5 × 10 5 to 3.7 × 10 8 cfu/mL, respectively.…”
Section: Microbiological Characteristicsmentioning
confidence: 99%
“…(Witthuhn et al, , 2005; Candida lipolytica, C. holmii ; C. inconspicua, C. maris ; C. kefyr (Motaghi et al, 1997;Witthuhn et al, 2004Witthuhn et al, , 2005; C. lambica, C. krusei, Cryptococcus humicolus (Witthuhn et al, 2005); Kluyveromyces marxianus (Garrote et al, 1998(Garrote et al, , 2001KokTas et al, 2012;Loretan et al, 2003;Simova et al, 2002); Klyveromyces lactis (Loretan et al, 2003;Magalhaes et al, 2011a); Saccharomyces cerevisiae (Garrote, Abraham, & De Antoni, 1997;Loretan et al, 2003;Magalhaes et al, 2011a;Motaghi et al, 1997;Simova et al, 2002;Witthuhn et al, 2004); S. fragilis, S. lactis (Motaghi et al, 1997); S. lipolytic (Garrote et al, 1997); Zygosaccharomyces rouxii, Torulaspora delbrus, Torulaspora delbrueckii, Debaryomyces hansenii (Loretan et al, 2003); Kazachstania aerobia, Lachancea meyersii (Magalhaes et al, 2011a); and Geotrichum candidum (Garrote et al, 1997;Witthuhn et al, 2005). Grønnevik et al (2011) found that the LAB count in kefir samples decreased during the first 4 weeks of storage, whereas yeast levels increased throughout the storage period.…”
Section: Microbiological Characteristicsmentioning
confidence: 99%
“…Acidity was also a determining variable in the time spent until formation of a stable clot, since the Ministry of Agriculture, Livestock, and Supply -MAPA (2007) establishes values between 0.6 and 2.0 g acid lactic.100 g -1 product for fermented milk, and for kefir it is recommended that acidity does not exceed 1 g lactic acid.100 g -1 product. Therefore, the Quark cheese had developed acidity near the maximum recommended by the MAPA (BRASIL, 2007), and a concentration of lactic acid (9.6 mg.mL -1 ) of about 10 times greater than the concentration (0.95 mg.mL -1 ) of lactic acid capable of neutralizing the action of pathogenic microorganisms, as observed in the studies of Garrote, Abraham and De Antoni (2001).…”
Section: Resultsmentioning
confidence: 82%
“…However, these proteins can be incorporated into the final product when using ultrafiltration, in which all coagulated milk is converted into cheese (FOX, 2001), a practice widely used on industrial scale in some countries (VEIGA; VIOTTO, 2001). …”
Section: Resultsmentioning
confidence: 99%
“…Alguns microrganismos estão sempre presentes no simbiótico, mas outros nem sempre são encontrados, dependendo do método de cultura e substrato utilizado. 7 Em culturas lácteas encontra-se um polissacarídio conhecido como quefirano, ou como fator de crescimento de quefir -KGF, que constitui um bioproduto carboidratado secretado por algumas bactérias presentes nos grãos de quefir e que permite o encapsulamento de suas cepas microbianas em uma matriz de polissacarídios. É um exopolissacarídio parcialmente solúvel em água, composto de unidades repetitivas de monossacarídios (galactose e glicose), na proporção de 1,1:0,9.…”
Section: Introductionunclassified